2017
DOI: 10.1148/radiol.2017160681
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor Imaging of the Physes: A Possible Biomarker for Skeletal Growth—Experience with 151 Children

Abstract: Purpose To determine the changes of diffusion-tensor imaging (DTI) and tractography in the distal femur and proximal tibia related to age, sex, and height. Materials and Methods Following institutional review board approval, with waiver of consent and with HIPAA compliance, the authors retrospectively analyzed DTI images of the knee in 151 children, 73 girls (median age, 14.1 years; range, 6.5-17.8 years) and 78 boys (median age, 16.6 years; range, 6.9-17.9 years), studied from January 2013 to October 2014. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…Jaimes et al found that in vivo DTI and tractography showed the columnar microstructure of the physis and adjacent metaphysis, and provides further insight into normal growth . Their extended study demonstrated that DTI and tractography in the distal femur and proximal tibia related to age, sex, and height . Our results agree with these findings that DTI and tractography can detect the arrangement and structural characteristics of the physis and adjacent metaphysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Jaimes et al found that in vivo DTI and tractography showed the columnar microstructure of the physis and adjacent metaphysis, and provides further insight into normal growth . Their extended study demonstrated that DTI and tractography in the distal femur and proximal tibia related to age, sex, and height . Our results agree with these findings that DTI and tractography can detect the arrangement and structural characteristics of the physis and adjacent metaphysis.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Achilles tendon diffusion properties of healthy participants and tendinopathy patients were investigated on a clinical MR scanner with the Achilles positioned at the magic angle (~55°) to main magnetic field for the maximum tendon MR signal . DTI of growing ends of long bones demonstrated the columnar structure in the physis and metaphysis of the knee . Tractography of the thin‐layer articular cartilage is still challenging because of the lower FA values compared to tendon and ligaments …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of the right knee was performed at 3 T (Verio; Siemens Medical Systems, Erlangen, Germany) using a 15-channel knee coil (Quality Electrodynamics, Mayfield Village, OH). DTI parameters were identical to those of previous studies of physeal DTI [16,17]. To assess reliability, we obtained two sagittal DTI sequences per participant.…”
Section: Mri Imaging Parametersmentioning
confidence: 99%
“…Cis-retinoic acid, a biological agent used to treat high-risk neuroblastoma, has a strong impact on physeal function resulting in reduced physeal thickness and disintegrated loss of columnar architecture [13][14][15]. Diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) are used to evaluate physeal and metaphyseal structure and function [16,17]. Previous studies in healthy subjects show that DTI depicts a region with tracts parallel to the main axis of the bone that coincides roughly with the physis and metaphyseal spongiosa.…”
Section: Introductionmentioning
confidence: 99%
“…The application of DTI to musculoskeletal system has been growing recently, but there are challenges for the knee joint, arising from the complex anatomy of knee joint, low FA values, and short T2/T2 values. DTI tractography has been used to detect the integrity of individual connective tissues, such as Achilles tendon, growth plate, and anterior cruciate ligament (ACL) graft in clinical scanners . Tractography of the articular cartilage in rat knee joint has also been reported with DTI at microscopic resolution …”
Section: Introductionmentioning
confidence: 99%